Teaching of Nuclear Cardiology in Times of Pandemic: Transfer of a Case-based Interactive Course from Classroom to Distance Learning - Bell, Laura; Lemos, Martin; Mottaghy, Felix M.; Lindner, Oliver; Heinzel, Alexander (Nuklearmedizin - NuclearMedicine, 2022)
Aim While methods of independent study, such as problem-based learning, have been shown beneficial to students’ learning outcome and motivation to self-educate, these concepts are currently challenged by the pandemic. The aim of the current study was the evaluation of the transfer of an interactive nuclear cardiology teaching module to an online, distance learning setting. Methods Two-hundred-forty medical students completed and evaluated the teaching module in a classroom and 127 students in the distance learning setting. Results The interactive, problem-based teaching module was transferred well into the distance learning setting during the pandemic. However, while the presented results suggest that distance learning is a good substitute for classroom teaching when in-person teaching is not possible, the distance teaching module was perceived less efficient in its course didactics, demands as well as applicability than the same module in a classroom setting. Conclusion Although distance learning thus cannot entirely replace classroom education, it does provide a well-suited alternative method to teach particularly nuclear medicine and medicine in general. Future applications should offer introductory sessions, provide learning materials in advance and slow down the teaching pace to facilitate online, distance learning.
Keywords: medizinische Lehre; Fernunterricht; Lernen auf Distanz; Nuklearkardiologie; Fallbasiertes Lernen